APLIKASI TEKNIK AAN DI REAKTOR RSG-GAS PADA PENENTUAN UNSUR ESENSIAL DAN TOKSIK DI DALAM IKAN DAN PAKAN IKAN - Yusuf, Saeful (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
This paper reported on the application of NAA (Neutron Activation Analysis) Technique in the determination of the concentration of the essential and toxic elements in some species of fish and fish feed. Determination of elements using instrumental NAA technique with comparison and k0-INAA methods. Samples were irradiated in the RSG-GAS which has a thermal neutron flux 5.0E +13 ncm-2s-1. The results showed that as many as 12 elements in 11 species of fish in the sea water and fresh water has been determined that As, Br, Cr, Co, Cs, Fe, Hg, K, Na, Rb, Se and Zn. For toxic elements, As concentrations in marine fish has exceeded the maximum limit of 1 mg / kg, Hg concentrations were still below the maximum limit of 0.5 mg / kg, both for marine fish and fresh water fish. K and Na elements is the macro esensial element while Cr, Co, Fe, Se and Zn elements are micro esensial elements. The concentration of minerals in marine fish higher concentration than fresh water fish. Br, Cs, and Rb are non-essential elements were identified in all analyze fish. The results also showed that all of the elements identified in the fish feed contained in fish. This suggests that fish feed contributes to the concentration of elements in freshwater fish.